Application and efficacy of beidellite clay for the adsorption and detoxification of deoxynivalenol (vomitoxin) - Johnson O. Oladele; Meichen Wang; Kelly J. Rivenbark; Timothy D. Phillips (Emerging Contaminants)
The incidence of mycotoxin occurrence throughout the entire lifespan of some agricultural products could be due to climatic conditions and environmental factors (including high temperature, drought, and heavy rainfall) that enhance growth of fungi. Deoxynivalenol (DON) which is also referred to as vomitoxin is a mycotoxin produced from many Fusarium species. DON ranks high among the prominent mycotoxins in cereal products and is a ubiquitous toxin in livestock feeds. DON's adverse effects present major health challenges in both livestock and humans. The use of natural sorbents including smectite clays, is an economically feasible strategy to mitigate mycotoxin toxicities. Previous studies have demonstrated the potential of edible clays as protective components of human food and animal feed to alleviate toxicity associated with short-term exposure to mycotoxins including DON. Hence, this study was designed to investigate the sorption mechanisms of DON onto the binding surfaces of beidellite clay, assessing essential binding parameters such as enthalpy, free energy, binding capacity, affinity, and plateau surface density. These markers were used to predict availability of DON under the experimental conditions. Furthermore, the protection of beidellite clay against DON-induced toxicity was carried out using living organisms susceptible to DON toxicity, including Hydra vulgaris and Lemna minor. These studies investigated the dose-dependent detoxification of DON by 0.05–2 % inclusion of beidellite. Beidellite exhibited more than 75 % protection in Lemna minor and 53 % in Hydra vulgaris validating that this clay is effective in detoxifying DON. During emergencies, or after disasters, inclusion of edible clay like beidellite in food, water or capsules could reduce bioavailability of DON and halt potential exposures to humans and animals.